What is the Level of Personal Health Knowledge of Grade VI Students? An Investigation on Upper Primary School Students - Insanistyo, Bayu; Nopiyanto, Yahya Eko; Ibrahim, Ibrahim; Kardi, Ipa Sari; Sandi, Bayu Nirwana (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
The purpose of this study was to determine the level of personal health knowledge of class VI students at SD Mangunharjo. The method used is descriptive quantitative. The population and research sample were all 18 students of class VI at SD Mangunharjo. The data collection technique uses a questionnaire consisting of 6 indicators. Data analysis technique uses descriptive quantitative by calculating the mean value and standard deviation. The results of the study stated that the level of student knowledge in terms of personal hygiene indicators was in the moderate category, the indicators of regular living habits were in the moderate category, the food indicators were in the moderate category, environmental hygiene was in the medium category, disease prevention was in the moderate category, and health examination is in the moderate category. It can be concluded that the level of personal health knowledge of class VI students at SD Mangunharjo is in the moderate category.